Significance of Six Minute Walking Distance in Predicting Functional Capacity Status of Patients with Pulmonary Hypertension Complicating an Atrial Septal Defect - Anggia Endah Satuti; Dyah Wulan Anggrahini; Lucia Krisdinarti (ACI (Acta Cardiologia Indonesiana), 2015)
Background: Six minute walk test (6 MWT) is a sub-maximal exercise test that measures an integrated response of all systems responsible during exercise. Pulmonary arterial hypertension (PAH) is a problem encountered by patients with atrial septal defect (ASD). Assessment of functional capacity in patients with PAH based on the WHO functional classifi cation remains a powerfulpredictor of survival in these patients. The World Health Organization functional classifi cation is a subjective tool because it is based on anamnesis of ordinary activity. On the contrary, 6 MWT is an objective tool to measure functional capacity of patients with pulmonary hypertension. Objective: To determine the walking distance obtained using 6 MWT as a measurement of functionalcapacity in ASD patients with PAH. Methods: A cross sectional study was used to determine the walking distance as a measurement of functional capacity in ASD patient with PAH. This study was a sub-study of an Atrial Septal DefectRegistry done in RSUP Dr. Sardijto, Yogyakarta, since 2012. Pulmonary arterial pressure was measured using Pulmonary Arterial Systolic Pressure (PASP) obtained from echocardiography. Pulmonary hypertension was divided into three categories based on PASP, mild with PASP of less than 45 mmHg, moderate with PASP of 45-59 mmHg and severe with PASP of more than 60 mmHg. All patients did 6 MWT to measure their functional capacity. The relationship between 6 MWT distance and severity of PAH was measured using Pearson correlation analysis. Results: Forty-three patients were included in this study with 32 female patients (74%) and 11 male patients (26%) with an age range of 17-70 years old. Forty-four patients (44%) with ASD had severe PAH. The mean of 6 MWT distance was 337 m. There were signifi cant differences between mild, moderate and severe PAH in correlation with the 6 MWT distance (p= 0.001). The patients with severe PAH had only 278 m walking distance compared to those with mild PAH who had 394 m walking distance. There was a significant relationship between the 6 MWT distance and severity of PAH (p=0.01). This study showed that 6 MWT correlates negatively with the severity of PAH. We found that the higher pulmonary arterial pressure, the shorter walking distance (p=0.01, r -0,506). Conclusion: ASD defect patients with severe PAH had shorter walking distance compared to those with mild PAH. The 6 MWT is a reliable and objective measurement of functional capacity for ASD patients with PAH.